The Effect of Financial Knowledge, Financial Attitude and Personality on Financial Behavior on Small Medium Crafts Micro Enterprises in Gresik District - Dimas Wiratama; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2022)
This study aims to determine the effect of financial knowledge, financial attitudes and personality on financial behavior in handicraft businesses in Gresik Regency. The sample in this study used the saturated sample method from a total population of 80, so the samples taken were 80 handicraft entrepreneurs in Gresik Regency. The data analysis technique used multiple linear regression analysis. The results of multiple linear analysis prove that financial knowledge, financial attitudes and personality partially influence financial behavior in handicraft business actors in Gresik Regency. handycrafts.